ACTIVATION OF REACTIVE OXYGEN SPECIES AND THE RENIN-ANGIOTENSIN SYSTEM IN IgA NEPHROPATHY MODEL MICE - Ohashi, Naro (2008)
1. Although IgA nephropathy is the most common form of primary glomerulopathy, the detailed mechanisms underlying its development remain uncertain. 2. In the present study, we used male high IgA strain of ddY (HIGA) mice as the IgA nephropathy model and age-matched male BALB/c mice as the control. Recent studies have demonstrated that reactive oxygen species (ROS)-dependent enhancement of the renin-angiotensin system (RAS) plays a potential role in the development and progression of renal injury. Therefore, in the present study we periodically measured the systolic blood pressure (SBP) of mice over the period 21-25 weeks of age and estimated markers for ROS, RAS and renal damage after mice had been killed at 25 weeks of age. 3. Markers for ROS (urinary 8-isoprostane excretion and renal 4-hydroxy-2-nonenal accumulation), RAS (renal angiotensinogen protein expression, urinary angiotensinogen excretion and renal angiotensin II) and renal damage (desmin-positive area and urinary protein excretion), as well as SBP, were significantly increased in HIGA mice compared with control BALB/c mice. 4. The data suggest that both ROS and the RAS are activated at an early phase in IgA nephropathy model mice.